Biomonitoring of airborne heavy metals using Brachychiton populneus (Schott & Endl.) leaves - Sabr, Halmat A. (Zanco Journal of Pure and Applied Sciences, 2023)
Trees growing close to emission sources have higher metal concentrations in their leaves, which is an indication of how polluted these location are. Additionally, the accumulation of heavy metals such as Fe, Zn, Cu, Cd, and Pb in various tree species has increased as a result of industrial and mining operations. The aim of the present study was to use Brachychiton populneus (Schott & Endl.) tree leaves as biomonitor to evaluate air pollution of Erbil city. Samples were collected from 6 different locations. Chlorophyll content, stomata number and heavy metals in leaves were determined. The result of the present study indicated that the highest mean of chlorophyll content was recorded for control (42.76), while there was not significant effect of pollution from traffic density was recorded for location 5. Non significant effect of roadsides of stomata density was observed in leaves. Surprisingly locations 2 showed that the leaves accumulated the lowest concentration of heavy metals as compare to control location. In addition, long side roads and parks, and the study species can has the capacity to accumulate the atmospheric pollution. As an alternative to other an expensive approaches thus may play an essential part in monitoring pollution of Erbil city. Finally the measurement characteristics may be employed as a bioindicator. It is also recommended to apply air pollution tolerance index (APTI) to determine suitability for selection of tree species as biomonitor and green belt plantations.